(untitled) (Modern education and development, 2025)
Мысли Фитрата о духовности, культуре, литературе, образовании и политике сейчас актуальны. Простые, но философские мысли в Фитрате никого не оставят равнодушным. Это помогает подняться в высоту. В других произведениях Мунаввара Кари умело освещались события жизни, повседневный образ жизни, политические процессы, что было признаком высокой духовности. Fitrat’s thoughts about spirituality, culture, literature, education and politics are now relevant. Simple, but philosophical thoughts in Fitrat will not leave anyone indifferent. It helps to rise in height. In other works of Munavvar Kari, life events, daily lifestyle, political processes were skillfully covered, which was a sign of high spirituality.